2017
DOI: 10.1681/asn.2017060694
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcomes after Early Initiation of RRT in Critically Ill Patients with AKI

Abstract: Whether earlier initiation of RRT in critically ill patients with AKI can improve outcomes remains debated. We examined follow-up data from a large clinical trial to prospectively investigate the long-term outcomes associated with the timing of RRT initiation in such patients. We extended the follow-up of patients in the Early Versus Delayed Initiation of RRT in Critically Ill Patients with AKI (ELAIN) Trial from 90 days to 1 year after randomization for 230 (99.6%) patients. The primary outcome was a composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 38 publications
(41 reference statements)
1
47
0
2
Order By: Relevance
“…More recently Meersch et al. examined the long‐term outcomes from follow‐up data in the ELAIN study . Early initiation of RRT in critically ill patients with AKI significantly reduced the rate of major adverse events (persistent renal dysfunction, dialysis dependence, mortality) at 1 year compared with delayed initiation of RRT (early initiation:delayed initiation = 50.2% vs 69.8%, P < .01).…”
Section: Rrt For Akimentioning
confidence: 99%
See 1 more Smart Citation
“…More recently Meersch et al. examined the long‐term outcomes from follow‐up data in the ELAIN study . Early initiation of RRT in critically ill patients with AKI significantly reduced the rate of major adverse events (persistent renal dysfunction, dialysis dependence, mortality) at 1 year compared with delayed initiation of RRT (early initiation:delayed initiation = 50.2% vs 69.8%, P < .01).…”
Section: Rrt For Akimentioning
confidence: 99%
“…One RCT and a few observational studies have focused on the impact of the initiation of RRT for AKI on long‐term (beyond 90 days) mortality or long‐term risk of ESRD. A recent cohort study conducted at Aarhus.…”
Section: Rrt For Akimentioning
confidence: 99%
“…By the end of 12 months of follow up, in the Early Versus Delayed Initiation of RRT in Critically Ill Patients with AKI (ELAIN) trial, they evaluated the impact of timing of RRT on the long‐term outcomes in such patients. The investigators concluded that early initiation of RRT in both stage 2 and stage 3 AKI reduced persistent renal dysfunction, dialysis dependence and mortality at 1 year (OR of 0.23 with early initiation; 95% CI = 0.11–0.45; P < 0.001) . The results from the extended study of Randomized Evaluation of Normal vs Augmented levels of RRT (POST‐RENAL) cohort found no benefit in long‐term mortality and ESRD progression based on the intensity of dialysis in the acute phase .…”
Section: Treatment Options To Reduce Progression To Ckd and Improve Lmentioning
confidence: 99%
“…The investigators concluded that early initiation of RRT in both stage 2 and stage 3 AKI reduced persistent renal dysfunction, dialysis dependence and mortality at 1 year (OR of 0.23 with early initiation; 95% CI = 0.11-0.45; P < 0.001). 78 The results from the extended study of Randomized Evaluation of Normal vs Augmented levels of RRT (POST-RENAL) cohort found no benefit in long-term mortality and ESRD progression based on the intensity of dialysis in the acute phase. 79 However, Bell et al, in collaboration with the Swedish Intensive Care Nephrology Group, concluded that CRRT compared with intermittent RRT had a bigger chance of renal recovery.…”
Section: General Measuresmentioning
confidence: 99%
“…An extended 1 year follow‐up of 230 patients in the Early v Delayed Initiation of RRI in critically Ill Patients (ELAIN) Trial found that the early group had significantly lower rates of mortality (50% vs 70%) and failure to recover renal function (29% vs 64%) than the late group …”
mentioning
confidence: 99%